Antlers Characterization for Identification of Deer Species (Family Cervidae) in Indonesia - Donan Satria Yudha; M Zulfiqar Meizar Pratama; Rury Eprilurahman (Journal of Tropical Biodiversity and Biotechnology, 2019)
There are five species of deer (family Cervidae) living in Indonesia today. Male deer possesses antlers, a unique character of male deer. Antlers have economic values for quite a long time. Antler’s growth is influenced by several factors, therefore each species of deer have its own unique antlers’ shape and size. Antler’s identification usually relies on size measurement and overall shape of complete antlers which still attach to the skull. It is difficult to identify shed, broken or individual antler. The purpose of the research is to understand antlers’ morphological characters on each species to become diagnostic characters. Specimens analysed were collections of LIPI and were analysed with Principal Component Analysis (PCA) using PAST3 software. The results showed each species of deer having their own unique antlers’ character, and so it can be used to determine the species of Indonesian deer. The important structures for identification are relief, pedicle, brow, bez, and main beam.